Outcome of Post-resection Intravesical BCG and Mitomycin C Therapy on Non-muscle Invasive High- Grade Transitional Cell Carcinoma of Urinary Bladder - Roy, Nikolas Chandra; Chowdhury, Md Shafiqul Alam; Karmaker, Uttam; Belal, Md Tawhid (Bangladesh Journal of Urology, 2022)
Objective: This study aimed to compare the outcome of postoperative intravesical BCG and Mitomycin C therapy on non-muscle invasive high grade superficial bladder tumor. Methods: This prospective quasi experimental study was carried out among the patients with non-muscle invasive high grade transitional cell carcinoma (TCC) of urinary bladder, who underwent complete transurethral resection of bladder tumor of primary tumor attended at the urology department of DMCH, during March 2017 to August 2019. After pre-operative evaluation and counselling, 70 patients with histologically documented high grade superficial bladder tumor were included and divided in two groups. We instilled intravesical BCG in one group and Mitomycin C (MMC) therapy in other group. The patients were followed up at 3rd ,6th , 9th , 12th and 18th month. Results: The mean age of BCG group was 55.8 years while 60.2years in MMC group with majority between 45 to 65 years (>80%). Sex distribution in both groups were almost equal (p=0.062). There were equal number of TaG3 and T1G3 disease in each group (p=0.809). Local adverse reactions were significant in BCG group (p= 0.016), among them UTI, between two groups, was statistically significant (p=0.039). Incidence of hematuria (p=0.324), voiding frequency (p=0.163) and local rash (P=0.642) had no statistically significant difference. The incidence of post-instillation systemic adverse reactions between two groups were statistically significant (p=0.034). Fever (p=0.028) was significant among them. Intavesical BCG was significantly more effective than MMC in terms of disease recurrence (p=0.047) and progression (p=0.008). Conclusions: We analysed the efficacy and safety of intravesical BCG and MMC in two groups, showing that BCG was more effective in terms of disease recurrence and progression but local and systemic side effects were higher in BCG group. Bangladesh J. Urol. 2021; 24(1): 62-71